CONTROL AND IMPLEMENTATION OF A MINI CYLINDRICAL-PARABOLIC SOLAR CONCENTRATOR (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This research presents the design and implementation of a solar concentration system utilizing a cylindrical parabolic solar concentrator. The system is designed to capture and focus sunlight onto a tube containing a heat transfer fluid. The resulting heat is harnessed to produce steam, which subsequently drives a steam turbine for electricity generation. A solar tracking mechanism ensures optimal system performance throughout the day. The core of the concentration system comprises a stepper motor integrated into the mechanical structure, with communication facilitated by an Arduino board and MATLAB. The control of the solar concentrator is implemented through two distinct strategies. The first is automatic control based on light-dependent resistors (LDRs), which are used to determine the sun's position. This data is transmitted to the control system, which enables automatic adjustment of the parabolic trough solar concentrator's orientation and positioning. The second one is a manual control based on a MATLAB graphical user interface (GUI), developed to enable manual control of the solar concentrator's stepper motor. This paper investigates the intricate relationship between control precision, error, and the number of motor steps.
Keywords: Solar concentration; Solar tracking; Stepper motor; Automatic control; Light Dependent Resistors